Combination therapy with AT1 blocker and vitamin D analog markedly ameliorates diabetic nephropathy: Blockade of compensatory renin increase - Zhang, Zhongyi (National Academy of Sciences, 2008)
The renin–angiotensin system (RAS) plays a critical role in the development of diabetic nephropathy, and blockade of the RAS is currently used for treatment of diabetic nephropathy. One major problem for the current RAS inhibitors is the compensatory renin increase, which reduces the efficacy of RAS inhibition. We have shown that vitamin D exerts renoprotective actions by transcriptionally suppressing renin. Here we demonstrated that combination therapy with an AT1 receptor blocker and a vitamin D analog markedly ameliorated renal injury in the streptozotocin (STZ)-induced diabetes model due to the blockade of the compensatory renin rise by the vitamin D analog, leading to more effective RAS inhibition. STZ-treated diabetic DBA/2J mice developed progressive albuminuria and glomerulosclerosis within 13 weeks, accompanied by increased intrarenal production of angiotensin (Ang) II, fibronection, TGF-β, and MCP-1 and decreased expression of slit diaphragm proteins. Treatment of the diabetic mice with losartan or paricalcitol (19-nor-1,25-dihydroxyvitamin D(2), an activated vitamin D analog) alone moderately ameliorated kidney injury; however, combined treatment with losartan and paricalcitol completely prevented albuminuria, restored glomerular filtration barrier structure, and markedly reduced glomerulosclerosis. The combined treatment suppressed the induction of fibronection, TGF-β, and MCP-1 and reversed the decline of slit diaphragm proteins nephrin, Neph-1, ZO-1, and α-actinin-4. These were accompanied by blockade of intrarenal renin and Ang II accumulation induced by hyperglycemia and losartan. These data demonstrate that inhibition of the RAS with combination of vitamin D analogs and RAS inhibitors effectively prevents renal injury in diabetic nephropathy.